Foreign experience of legal regulation of public administration in emergencies and martial law: lessons for Ukraine in the third year of wartime - Honcharenko , Hanna (Pressing Problems of Public Administration, 2024)
This article analyzes the foreign experience of legal regulation of public administration in emergencies and martial law, with a focus on lessons for Ukraine during the third year of war. The study highlights the unprecedented challenges facing Ukraine, including a prolonged war, large-scale destruction, and a humanitarian crisis, underscoring the relevance of this research. The author conducts a comparative analysis of crisis public administration models in countries such as Israel, Croatia, Georgia, South Korea, the United Kingdom, and Japan. Based on this analysis, the key principles of successful crisis management are identified, including flexibility, adaptability, attention to communication, and innovation. The article outlines how these practices can be adapted to the Ukrainian context. Specifically, it explores the potential for implementing Israel’s decision-making analytical infrastructure, Croatia’s reintegration experience, Georgia’s digitalization of public services, and South Korea’s strategic planning approach. At the same time, the author emphasizes that the mechanical adoption of foreign practices without considering Ukraine’s unique cultural, political, and economic characteristics may be ineffective. A creative approach and inclusive public dialogue are necessary to build a sustainable and adaptive public administration system in Ukraine. Attention is also given to global transformations affecting public administration systems: the breakdown of the international order, the rapid development of digital technologies, and the crisis of traditional educational models. The article argues that effectively addressing modern challenges requires not only institutional changes but also a deep transformation of administrative culture, the development of crisis communication strategies, institutional capacity-building, and the adoption of artificial intelligence technologies. The conclusions emphasize the uniqueness of the Ukrainian context, which creates opportunities for innovative approaches to crisis management. Ukraine has the potential to become a model of successful democratic transition and a leader in regional integration if it strategically assesses and adapts the best practices of other countries.